Tindakan Yang Dilakukan Terhadap Kejahatan Abortus Provocatus Menurut Kitab Undang-Undang Hukum Pidana - Salim Fauzi (Universitas Muhammadiyah Sumatera Utara, 2019)
The regulation of abortion in positive law in Indonesia is contained in two laws, namely the Criminal Code (KUHP) Article 299, 346, 347, 348 and 349 and regulated in Law No. 36 of 2009 concerning Health Article 75, 76.77. There is a difference between the Criminal Code (KUHP) and the Law with the formulation of a problem, namely 1. How is the Legal Regulation of Crime Abortus Provocatus? 2. Law Enforcement Against Crime of Abortus Provocatus According to Criminal Law The research method used in this study is the approach used to this problem The research material was obtained through a normative juridical approach namely legal approach by looking at regulations, both primary law and secondary law or approach to problem by looking at the prevailing laws and regulations, literature, scientific work and opinions of experts and so on.